Not throwing away my shot: an analysis of shot features in men`s collegiate water polo - Gullikson, J.; Mayberry, J. K.; Gale, L. R.; Killick, L. (International Journal of Performance Analysis in Sport, 2020)
The purpose of this paper is to identify the important features of "high-quality" shots in water polo. The lead author collected a sample of over 5000 shots from the men`s 2016-2017 NCAA seasons of play to train a logistic model for predicting goal-scoring probabilities. The results suggest that the odds of scoring decrease by about 29% for each additional metre of distance from centre-cage and by about 2% for each additional degree in angle of displacement from centre-pool, while side is not significant. Left-hand and skip shots are significantly more effective than right-hand and other shot types. Power plays double scoring odds compared with even play while uncontested shots more than double odds compared with fully contested shots. Overall, the five most important variables in the model were distance, skip, power play, contested, and angle. The paper also links to an online application that estimates shot quality for different user-input scenarios. Players and coaches can apply this app to evaluate team and opponent performance in future contests. As an example, the shooting performance of the top four NCAA teams from the sampled seasons is analysed to determine if they won games by taking high-quality shots or through above-average shooting performance.